Assessment of feedwater hardness effects on thermal efficiency of an industrial fire-tube boiler - Hasan Bashori; Wisnu Subrianto (Jurnal Polimesin, 2026)
Boiler efficiency remains an important factor in industrial energy management, where feedwater quality can directly influence heat transfer performance and fuel consumption. This study evaluates the relationship between feedwater hardness and the thermal efficiency of an industrial fire-tube boiler operating under actual industrial conditions. Operational data were collected over a 30-day observation period, including feedwater hardness, steam production rate, natural gas consumption, and boiler thermal efficiency. The boiler performance was initially assessed using engineering-based calculations, including steam energy output, fuel energy input, gas-to-steam ratio, and direct efficiency evaluation. Statistical methods, including Pearson correlation, linear regression, and multiple regression, were then applied to strengthen the analysis. The results indicate that feedwater hardness exhibited a strong negative statistical association with boiler thermal efficiency. The linear regression analysis produced a coefficient of determination of approximately R² = 0.96, indicating that variations in feedwater hardness were strongly associated with changes in thermal efficiency under relatively stable operating conditions. Lower hardness levels were also associated with lower fuel consumption and improved gas-to-steam ratios. Multiple regression analysis further indicates that steam production and fuel consumption also contribute to boiler efficiency. These findings provide field-based evidence supporting the importance of feedwater treatment in maintaining efficient industrial boiler performance.